2018
DOI: 10.1016/j.jhsa.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Damage in a Distal Radius Fracture Model Treated With Locked Volar Plating After Simulated Postoperative Loading

Abstract: Microstructural damage or a loss of fixation due to an overly rigid volar plate design may cause malunion or nonunion of fracture fragments and lead to bone-implant instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…On the other hand, for the biomechanical tests using synthetic radii, the variability in the measured stiffnesses could be related to the biomechanical apparatus. To ensure the improvement of the new biomechanical apparatus, the SD of measured stiffnesses using the new biomechanical apparatus was compared with those of previous studies (Hsiao et al [ 5 ]; Salas et al [ 6 ]; Yamazaki et al [ 7 ]; Zysk and Lewis [ 8 ]; Neder Filho et al [ 9 ]; Oh et al [ 10 ]), as shown in Table 2 . The SD of stiffnesses from the new biomechanical apparatus (i.e., ±15.3 N/mm) was significantly lower than those of previous studies, i.e., ±56 to ±112 N/mm for cadaver radii [ 5 , 6 , 7 ], and ±34 to ±274 N/mm for synthetic radii [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for the biomechanical tests using synthetic radii, the variability in the measured stiffnesses could be related to the biomechanical apparatus. To ensure the improvement of the new biomechanical apparatus, the SD of measured stiffnesses using the new biomechanical apparatus was compared with those of previous studies (Hsiao et al [ 5 ]; Salas et al [ 6 ]; Yamazaki et al [ 7 ]; Zysk and Lewis [ 8 ]; Neder Filho et al [ 9 ]; Oh et al [ 10 ]), as shown in Table 2 . The SD of stiffnesses from the new biomechanical apparatus (i.e., ±15.3 N/mm) was significantly lower than those of previous studies, i.e., ±56 to ±112 N/mm for cadaver radii [ 5 , 6 , 7 ], and ±34 to ±274 N/mm for synthetic radii [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical tests using a cadaveric radius can provide the actual interaction between implant and DRF; therefore, the cadaveric radius has been used for biomechanical tests. Unfortunately, the high variabilities in geometry and material properties of cadaveric radii can cause significantly high deviations of stiffness [ 5 , 6 , 7 ]. To avoid high variabilities in geometry and material properties, as well as to accommodate the special handling requirements of cadaver radii, the synthetic radius was designed to simulate structural and material properties of cadaveric radius, while providing the low variabilities in geometry and material properties, as well as fulfilling the simple handling requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall et al 28 compared VLP composition in a C3 DRF model using cyclic loading from 20 N to 230 N for 6000 cycles. Salas et al 26 compared VLP designs in an A3 DRF model using cyclic loading from 50 N to 250 N for 5000 cycles. When comparing 1 row to 2 rows of distal screws in a VLP, Tsutsui et al 29 used a C2 DRF model under cyclic loading from 0 to 250 N for 3000 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…25 The loading parameters were previously described to simulate postoperative rehabilitation loads following DRF fixation. 26 Specimens were preloaded to 50 N for 30 seconds then were sinusoidally compressed from 50 to 250 N at 1 Hz for 5000 cycles to simulate light active weight bearing during the immediate postoperative period. 26…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation